In Vitro Effect of Warm Air Stream Solvent Evaporation Method on Microtensile Bond Strength of the Fifth Generation Adhesive Systems - Navaei, Fathemeh; Shakerian, Mohaddesseh; Sameie, Ayda; Taram, Saman (Journal of Dental School, 2024)
Objectives This study aimed to evaluate the effect of warm air solvent evaporation on microtensile bond strength of composite restorations bonded with fifth-generation adhesive systems. Methods Twenty-four sound human molars were randomly assigned into two groups according to the type of bonding adhesive used: Adper Single Bond (3M ESPE, USA) or Solobond M (VOCO, Germany) (N = 12). Subsequently, each group was randomly divided into three subgroups according to the solvent evaporation time (0, 5, and 20 minutes). Composite build-ups were conducted incrementally on the dentin substrate fixed in a circular mold. Micro-tensile bond strength evaluation was conducted using the Isomet microtensile machine. Statistical analysis was performed using one-way ANOVA, Tukey’s, and Student’s t-test at p<0.05. Results At 20 minutes, Maximum and minimum microtensile bond strength were observed in Adper single bond and Solobond M , respectively. The mean microtensile bond strength of Adper single bond and Solobond M adhesives during 20 minutes of solvent evaporation were significantly different (p < 0.05). Conclusion In both ethanol and water-based adhesives, increasing the solvent evaporation time enhanced the microtensile bond strength. In contrast, in acetone-based adhesives, the optimum amount of solvent with other components must be present in the bonding solution to maintain bonds